Answer: x = - 2, y = - 4
Explanation:
The given system of equations is expressed as
2x + 5y = −24- - - - - - - - - - - - 1
3x − 5y = 14- - - - - - - - - - - - - - 2
We would eliminate x by multiplying equation 1 by 3 and equation 2 by 2. It becomes
6x + 15y = - 72
6x - 10y = 28
Subtracting, it becomes
15y - - 10y = - 72 - - 28
25y = - 100
Dividing the left hand side and the right hand side of the equation by 25, it becomes
25y/25 = - 100/25
y = - 4
Substituting y = - 4 into equation 1, it becomes
2x + 5 × - 4= −24
2x - 20 = 24
2x = - 24 + 20 = - 4
x = - 4/2 = - 2